Supporting stabilization in Libya: The challenges of finalizing and implementing the Skhirat agreement - Wolfram Lacher (Stiftung Wissenschaft und Politik (SWP), 2015)
Representatives of Libya's warring parties are close to reaching a UN-mediated power-sharing agreement that would establish a Government of National Accord (GNA). Assuming it is finalized, the deal will be fragile. Its implementation will be fraught with tensions and can collapse at any moment under pressure from spoilers. Reaching a final agreement and implementing it will require yet stronger political and diplomatic efforts from external actors. This includes intensive engagement with the parties to the agreement and those who oppose the deal or have been left out of it; carefully wielding the instrument of targeted sanctions; and containing regional rivalries that have fueled Libya's conflicts. International support for implementation should take into account not only the formal demands of a unity government but also wider Libyan sensitivities over external interference. A foreign military presence would undermine the agreement. (SWP Comments)
Keywords: 320